Post-exercise Warm or Cold Water Immersion to Augment the Cardiometabolic Benefits of Exercise Training: A Proof of Concept Trial - Brooke M. Russell; Brooke M. Russell; Courtney R. Chang; Courtney R. Chang; Terry Hill; James D. Cotter; Monique E. Francois; Monique E. Francois (Frontiers in Physiology, 2021)
We investigated whether substituting the final half within 60-min bouts of exercise with passive warm or cold water immersion would provide similar or greater benefits for cardiometabolic health. Thirty healthy participants were randomized to two of three short-term training interventions in a partial crossover (12 sessions over 14–16 days, 4 week washout): (i) EXS: 60 min cycling 70% maximum heart rate (HRmax), (ii) WWI: 30 min cycling then 30 min warm water (38–40°C) immersion, and/or (iii) CWI: 30 min cycling then 30 min cold water (10–12°C) immersion. Before and after, participants completed a 20 min cycle work trial, V.O2max test, and an Oral Glucose Tolerance Test during which indirect calorimetry was used to measure substrate oxidation and metabolic flexibility (slope of fasting to post-prandial carbohydrate oxidation). Data from twenty two participants (25 ± 5 year, BMI 23 ± 3 kg/m2, Female = 11) were analyzed using a fixed-effects linear mixed model. V.O2max increased more in EXS (interaction p = 0.004) than CWI (95% CI: 1.1, 5.3 mL/kg/min, Cohen’s d = 1.35), but not WWI (CI: −0.4, 3.9 mL/kg/min, d = 0.72). Work trial distance and power increased 383 ± 223 m and 20 ± 6 W, respectively, without differences between interventions (interaction both p > 0.68). WWI lowered post-prandial glucose ∼9% (CI −1.9, −0.5 mmol/L; d = 0.63), with no difference between interventions (interaction p = 0.469). Substituting the second half of exercise with WWI provides similar cardiometabolic health benefits to time matched exercise, however, substituting with CWI does not.